The More the Merrier? Diversity and Private Equity Performance - Benjamin Hammer; Silke Pettkus; Denis Schweizer; Norbert Wünsche (British Journal of Management, 2022)
This paper explores how diversity among lead partner teams (LPTs) of private equity (PE) funds affects buyout performance. We argue that there is a trade-off between the `bright side' of diversity (i.e. improved decision-making due to a broader set of perspectives) and the `dark side' (i.e. deteriorated decision-making due to a potential for clashes and a lack of cooperation). Our theoretical framework suggests that the net effect on performance depends on whether LPTs are diverse in socio-demographic or occupational aspects. To test this hypothesis, we develop a comprehensive index that measures LPT diversity along six dimensions. Using a sample of 241 buyouts and 547 involved PE partners, we find that higher scores in the socio-demographic component (gender, age, nationality) are associated with higher deal returns and multiple expansions. The opposite is true for higher scores in the occupational component (professional experience, educational background, university affiliation). Further results suggest that the `bright side' of diversity gets relatively more important in case of complex buyouts and uncertain deal environments.
Keywords: 650